Active methodologies in Music Education: Conceptions and practices in distance higher education - Cernev, Francine Kemmer (Revista Hipótese, 2022)
This article aims to describe the reflection of undergraduate music students on the practice guided by active methodologies in the distance education course. The research took place within the Strategies in Distance Learning course through action research. Of the 142 students enrolled in the discipline, the teacher and tutor participated in the study. The discipline's core was to explore how active methodologies and digital technologies could foster the active participation of students in their learning process and suggest possible changes in their pedagogical practices. The assumptions of collaborative learning, motivation to learn, learning strategies, and active methodologies in education guided de actions in the dynamics of teaching during the course. The results showed that articulating knowledge, dialogue, and technological mediation promoted participants' motivation, training, and musical development. Overall, the usage of active methodologies expands music-making possibilities to promote and support teacher training in distance education.
Keywords: Active methodologies; Collaborative learning; Distance education